Bridging the gap: Examining parental involvement strategies and their impact on homework completion rates in mathematics - Martin Jr. Nobis; Catherine L. Caparroso (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This research examines the influence of parental involvement tactics on students' mathematics homework completion rates, aimed at pinpointing crucial factors and evaluating the efficacy of such strategies. Utilizing a qualitative-quantitative approach, including with students, parents, and teachers, the study identifies distractions, workload, family obligations, and insufficient teacher support as significant barriers to mathematics homework completion. Time management, comprehension, and fatigue also play minor roles. The findings indicate that targeted parental involvement strategies can significantly enhance completion rates, with effective methods including accessible support, designated study spaces, breaking down assignments, fostering student autonomy, and leveraging technology. Additionally, parental involvement fosters stronger parent-child relationships, boosts student confidence, and promotes a positive attitude toward mathematics. To create a conducive learning environment, schools, teachers, and parents should collaborate, implementing recommendations such as creating quiet areas, promoting digital detox initiatives, managing workload, offering targeted support, establishing study environments, and setting clear expectations for mathematics practice.